The Existential Identity of Creativity in Islamic Philosophy: Intercultural Analysis of the Perfection of the Human Soul - Nuredin Mahmoudi (Dinamika Ilmu, 2023)
This research aims to investigate the existential identity of creativity in Islamic philosophy. In order to achieve the goals of the research, the analytical-inferential method has been used. The findings of the research showed that Mullah Sadra considers creativity as a part of the human soul, that is, he considers it as one of the platforms for realizing personal perfection and becoming a human being, and even above that, he considers creativity as a platform for the possibility of reaching the highest existential perfection, i.e. reaching It refers to true love and encountering a true lover. According to the mentioned contents, Mulla Sadra has a different definition of creativity. Creativity has a high position in Mulla Sadra's philosophy and he considers it a kind of godliness and has a wide scope for it. Creativity is considered a part of the human soul, and humans have an existential form that requires creativity. That existential form of the human soul, which is the source of all three creativity, creative person, and creative work. In Mulla Sadra's philosophy, the soul, as the first order of existence, has the most and strongest closeness to the body. Mulla Sadra considers the soul and the body as necessary and the soul cannot exist independently of the body. The human spirit has the ability to create, and this capability leads to human evolution.